A broadband dual circularly polarized shared‐aperture antenna array using characteristic mode analysis for 5G applications. Issue 3 (23rd January 2021) - Gao, Kai; Ding, Xiaoxiang; Gu, Li; Zhao, Yanwen; Nie, Zaiping
Abstract: A novel broadband dual circularly polarized (CP) array based on metasurface structures is proposed in this article. Four rotated metasurface elements fed with 90° phase difference are employed in this design, and crossed L‐shaped probes are used to achieve dual CP operation for each element. The proposed metasurface is shared by the closely spaced radiation elements to realize a compact size of only 0.69 × 0.69 × 0.03λ0, where λ0 is the free‐space wavelength at the lowest frequency of 3.5 GHz. The working mechanism of the proposed metasurface antenna element is investigated by using characteristic mode analysis. A prototype is fabricated and measured to confirm the effectiveness. The measured results show that the proposed antenna exhibits attractive features of wide operation bandwidth and good dual CP performance, which makes it suitable for 5G applications.